Lignin-assisted direct exfoliation of graphite to graphene in aqueous media and its application in polymer composites - Liu, Wanshuang (2016)
In this work, graphene is facilely prepared by direct exfoliation of graphite in aqueous media with the assistance of alkali lignin (AL). The graphite is successfully exfoliated into single- and multi-layer graphene, with about 20% monolayer ones, and the concentration of graphene in the aqueous dispersions can reach 0.65 ± 0.03 mg mL−1. The nanosheets are stabilized in the dispersions owing to π–π interaction between the graphene and AL, and the electrostatic repulsion between negative charged AL, as verified by fluorescence and zeta-potential measurements. The results also show that there are very few defects in the basil-plane of the graphene so that the free-standing graphene films prepared from the dispersions exhibit good electrical conductivity. Finally, the addition of only 0.1 wt% such graphene sheets to an epoxy resin gives 15%, 49%, and 97% enhancement in tensile strength, critical stress intensity factor and critical strain energy release rate, respectively.